Increasing Radiographers' Knowledge Through Socialization of Research Results Pocket Book in The Radiology Unit of Reksodiwiryo Hospital in Padang - Nansih, Livia Ade; Sari, Oktavia Puspita; Chairunnisa, Chairunnisa; Mareta, Santa; Dewilza, Nerifa; Hanifah, Wahdini; Artitin, Cicilia; Yudha, Sagita (PT. Hafasy Dwi Nawasena, 2024)
Radiology is a medical science that focuses on imaging technology. with results in the form of images /images for. to establish a diagnosis by looking at parts of the human body using X-rays so as to be able to provide professional examination services. The results of research that have been conducted at Aulia Hospital regarding the selection of CT scanogram settings for head scans with clinical chepalgia using the upper limit of the vertex and the lower limit of the mandibular because the location of the abnormality in the patient is not known whether in the nerve or sinus, if the scanogram is made to the lower limit of the petrous pars it still cuts the cerebrum so that the sinuses are still cut. whereas in the Radiology installation of Reksodiwiryo Padang Hospital uses a scanogram of the lower limit of the cranii base and the upper limit of the vertex to minimize the radiation received by the patient. Based on this, socialization activities through a pocket book of research results were carried out at Reksodiwiryo Padang Hospital on August 10, 2023 starting at 08.00 - 12.00 WIB, with participants being radiographers in the Radiology installation of Reksodiwiryo Padang Hospital. The methods used were lecture, discussion and question and answer. With communication that is two way traffic, there is a direct reciprocal relationship between the speaker and the participants or vice versa. This method applied can focus the attention of participants in training to develop thinking power and skills to express opinions in the form of exchanging information in solving a problem. The results of the socialization of the pocket book of research results on the effectiveness of CT scan management of the head with clinical chepalgia were 98% able to increase radiographers' knowledge in the selection of scanogram settings on CT scans of the head with chepalgia able to produce images that enforce dignosa